Ripples on the cosmic ocean : an environmental history of our place in the solar system - Degroot, Dagomar (The Belknap Press of Harvard University Press, 2025)
"Changes in cosmic environments, from solar storms to asteroid impacts, have altered the course of history. Tracing how such events shaped geopolitics and spurred scientific and cultural innovation, Dagomar Degroot asks what comes next as the solar system becomes increasingly vulnerable to human activity."--